If it's not what You are looking for type in the equation solver your own equation and let us solve it.
4-2(2w-3)=6w-90
We simplify the equation to the form, which is simple to understand
4-2(2w-3)=6w-90
Reorder the terms in parentheses
4+(-4w+6)=6w-90
Remove unnecessary parentheses
+4-4w+6=+6w-90
We move all terms containing w to the left and all other terms to the right.
-4w-6w=-90-4-6
We simplify left and right side of the equation.
-10w=-100
We divide both sides of the equation by -10 to get w.
w=10
| -6-4=-7a-5 | | 5/2x=(x-5) | | y=3sinx+2cosx | | a+a+5.80+0.5(5.80+a)+3(0.5(5.80+a))=246.20 | | 5+3(n+1)=2n | | 5z^2(z^2+2)=24-16z^2 | | -6x+10=15-6x | | 3x(2+3y)= | | 5-4(10+8m)=39+5m | | (5x)/(3iy)=5-6i | | x(x+3)-6(x+3)=0 | | (y-x)(y+11x)=a^2-b^2 | | c+8+2c=-10 | | -60=-6+6a | | (y-x)(y+11x)=y^2-x^2 | | -0.151-0.008n=4.1 | | 3y-9+3-4y=y+y-18 | | -0.151=-0.008x+4.15 | | 8.3x-3.1(x-4)=-29.04 | | X=0.75+0.35 | | (x-5)(4x-9)=0 | | 5+1.5(d-1)=0.5 | | n^2+4n-10=0 | | 12m=20m+80 | | 3-4(x-2)=8x(2x-1) | | 4(x-3)+8=4(2x-6) | | (x+2)-(59-x)= | | 5-4a=a-13+-1a | | p=36inches | | (x+2)+(59-x)= | | m/2-3=-18 | | 3(10*2x)=25 |